Weak Investment Law Enforcement in Land and Forest Fire Cases in Indonesia - Wuryandari, Utji Sri Wulan; Chairani, Anggi Dewinta; Safitri, Myrna Asnawati (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2022)
This article aims to analyze the formulation of sanctions in Indonesian investment law against foreign investors who commit environmental damage and pollution in the case of forest and land fires. This paper uses a legislative approach by analyzing the quality of legal norms on regulating sanctions for foreign investors involved in forest and land fires. The results show that the current development of global investment law requires companies, including transnational companies, to carry out environmental responsibilities in addition to social responsibility and good governance. The need to build pro-environmental investment law is important to strengthen environmental law enforcement with a multi-door approach. This is not followed by the investment law in Indonesia. The country's Investment Law does not strictly regulate sanctions against investors who violate their obligations and responsibilities to maintain the environment. The aspect of government supervision of the implementatio of investor obligations is also weak. These weaknesses in legal substance show that investment law is not in line with today's investment objectives that require support for environmental preservation or better known as green investment. This paper concludes that investment law will not be effective in supporting law enforcement in forest and land fire cases due to the lack of sanction formulation and weak supervision. Because of this, the existing investment law is still far from the goal of realizing green investment in Indonesia.